Activity features of tropical cyclone in Truong Sa archipelago region, Khanh Hoa province - Mau, Le Dinh; Dung, Nguyen Thi Thuy; Hoan, Pham Sy; Tuan, Nguyen Van; Cong, Nguyen Chi; Bac, Phan Thanh; Thanh, Nguyen Duc (Vietnam Journal of Marine Science and Technology, 2019)
This paper presents the study results of occurrence feature of tropical cyclone in Truong Sa archipelago region in the period from 1884 to 2018. Data on tropical cyclone such as storm track, intensity... were taken from the website www.weather.unisys.com/hurricane (National Weather Service, USA). The study results show that the study region is the most active area of tropical cyclone activity with about 1.61 times/year. The occurrence frequency of tropical cyclone was increasing from 1988 to 2018. The period from 1884 to 1944 the occurrence frequency of tropical cyclone was about 1 time/year, from 1945 to 2018 the occurrence frequency of tropical cyclone was higher at about 2.4 times/year. Especially, in the years of 2013 and 2017, tropical cyclone occurred 6 times/year. In the years of 2008, 1998, 1993, 1983, 1962, it occurred 5 times/year. The study region underwent the effect of two tropical cyclone seasons, the main season was from September to January of the next year with the occurrence frequency of tropical cyclone being about 4 times higher than that of the season from March to August. The period of highest occurrence frequency of tropical cyclone was from October to December whereas the lowest occurrence frequency of tropical cyclone was in July. The main season of tropical cyclone activity coincided with strong Northeast monsoon period.